Single‐Particle Entanglement. Issue 10 (6th September 2020) - Azzini, Stefano; Mazzucchi, Sonia; Moretti, Valter; Pastorello, Davide; Pavesi, Lorenzo
Abstract: This review is about single‐particle entanglement. Entanglement occurs when the state of a quantum system with at least two degrees of freedom has a particular non‐separable form. In the case of single‐particle entanglement, this quantum correlation is shared by the same particle being it a photon, a neutron, an ion, or an atom. Here, the basics of quantum entanglement are discussed focusing on the case it is related to the degrees of freedom of a single particle. It is discussed how the violation of peculiar inequalities in this context rules out any realistic non‐contextual hidden variable theory alternative to quantum mechanics. Moreover, experiments that demonstrate single‐particle entanglement for photons, neutrons, and atoms are discussed. Finally, the applications of single‐particle entanglement as a resource for quantum information are discussed and specifically quantum key distribution is detailed, where the use of single‐particle entangled photons allows to improve the security of the BB84 protocol. Abstract : This review addresses a peculiar type of entanglement involving two different degrees of freedom of a single particle. Through the description of bipartite systems, the concept of non‐contextuality is introduced in relation to Bell inequalitiy. The violation of it is demonstrated in experiments using photons, neutrons, and atoms. Applications to quantum key distribution and quantum information are also discussed.